Are number fields determined by Artin L-functions? - Klüners, Jürgen; Nicolae, Florin (Journal of Number Theory)
Let k be a number field, K/k a finite Galois extension with Galois group G, χ a faithful character of G. We prove that the Artin L-function L(s,χ,K/k) determines the Galois closure of K over $\ℚ$. In the special case $k=\ℚ$ it also determines the character χ.
Keywords: Algebra and Number Theory

Event Driven Modeling and Characterization of the Second Order Voltage Switched Charge Pump PLL - Ali, Ehsan; Hangmann, Christian; Hedayat, Christian; Haddad, Fayrouz; Rahajandraibe, Wenceslas; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

Influence of Traps on the Characteristics of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fabio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Self-aligning integration technique for organic electronics - Meyers, Thorsten; Vidor, Fabio F.; Kaijage, Shubi F.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg K.N.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microstructured Metal Layers in Dye Sensitized Solar Cells - Kleine, Andre; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

ZnO nanoparticle thin-film transistors on flexible substrate using spray-coating technique - Vidor, Fábio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Nanomaterials)
Keywords: General Materials Science; General Chemical Engineering

Ternary quadratic forms over number fields with small class number - Kirschmer, Markus; Lorch, David (Journal of Number Theory)
We enumerate all positive definite ternary quadratic forms over number fields with class number at most 2. This is done by constructing all definite quaternion orders of type number at most 2 over number fields. Finally, we list all definite quaternion orders of ideal class number 1 or 2.
Keywords: Algebra and Number Theory

Organic Field-Effect and Nanoparticle Thin-Film Transistors: Static Model - Romero, Adrian; Gonzalez, Jesus; Hilleringmann, Ulrich; Gloesekoetter, Peter (ANALOG 2016; 15. ITG/GMM-Symposium)

Influence of UV irradiation and humidity on a low-cost ZnO nanoparticle TFT for flexible electronics - Vidor, F. F.; Meyers, T.; Hilleringmann, Ulrich; Wirth, G. I. (2015 IEEE 15th International Conference on Nanotechnology (IEEE-NANO))

Improved rf design using precise 3d near-field measurements and near-field to far-field transformations - Hangmann, C; Mager, T; Khan, S; Hedayat, C; Hilleringmann, Ulrich (Smart System Integration-International Conference and Exhibition on Integration Issues of Miniaturized Systems)

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Definite quadratic and hermitian forms with small class number (Habilitation) - Kirschmer, Markus
Die Gitter von Klassenzahl eins oder zwei sind hier verfügbar: http://www.math.rwth-aachen.de/~Markus.Kirschmer/forms/

Cohen-Macaulay modules over some non-reduced curve singularities - Burban, Igor; Gnedin, W. (Journal of Pure and Applied Algebra)

Are mathematical problems boring? Boredom while solving problems with and without a connection to reality from students’ and pre-service teachers’ perspectives - Schönherr, Johanna; Schukajlow, S. (Proceedings of the 40th Conference of the International Group for the Psychology of Mathematics Education)

Erweiterung des Raman-Nath-Modells zur Analyse von Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (Technisches Messen)

ReconOS - Agne, Andreas; Platzner, Marco; Plessl, Christian; Happe, Markus; Lübbers, Enno (FPGAs for Software Programmers)
In this chapter, we present an introduction to the ReconOS operating system for reconfigurable computing. ReconOS offers a unified multi-threaded programming model and operating system services for threads executing in software and threads mapped to reconfigurable hardware. By supporting standard POSIX operating system functions for both software and hardware threads, ReconOS particularly caters to developers with a software background, because developers can use well-known mechanisms such as semaphores, mutexes, condition variables, and message queues for developing hybrid applications with threads running on the CPU and FPGA concurrently. Through the semantic integration of hardware accelerators into a standard operating system environment, ReconOS allows for rapid design space exploration, supports a structured application development process and improves the portability of applications between different reconfigurable computing systems.

Using Just-in-Time Code Generation for Transparent Resource Management in Heterogeneous Systems - Riebler, Heinrich; Vaz, Gavin Francis; Plessl, Christian; Trainiti, Ettore M. G.; Durelli, Gianluca C.; Bolchini, Cristiana (Proc. HiPEAC Workshop on Reonfigurable Computing (WRC))

Microdisk Cavity FDTD Simulation on FPGA using OpenCL - Kenter, Tobias; Plessl, Christian (Proc. Workshop on Heterogeneous High-performance Reconfigurable Computing (H2RC))